My First Year of Physical Education and Sport Teaching - Sinan Uğraş; Mehmet Güllü; Mehmet Akif Yücekaya (Anı Publishing, 2019)
In this research, ıt is aimed that the analysis of the problems the physical education teachers encounter at their jobs first approach years. Fenomenologic research from qualitative research methods is used. Samples of the research is composed of the physical education teackers who work at school connected to Adıyaman National Education Directorate. By using similar sample methods for choosing participants, two differerent focus group interviews are done. Content analysis is used for data analysis. Acording to research findings, three themes such as 'the problems arising from undergroduate education', 'inadequate sport substructure', 'and 'expectation and rapport problems' are established. In this research; because of the deficients of undergroduate education, physical education teachers experience some problems and in addition this, ıt is stated that due to the sport substructure inadequacy at schools, teachers experience some problems when they do activity. In their first years, it is determined that teachers have expactation and rapport problems such as cultural diversity, not make real their wishes concultant deficiency.